Peran Kegiatan Eksperimen Sains Sederhana dalam Mengembangkan Rasa Ingin Tahu Anak Usia Dini - Jannah, Haeratul; Fatimah, Nurul; Savna, Savna; Restuti, A.Nidha Eka (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2026)
Early Childhood Education (PAUD) faces challenges in stimulating children's innate curiosity during the golden age, where learning often prioritizes conventional activities like reading and counting, neglecting direct experience-based science approaches. This study aims to examine the role of simple science experiments in developing early childhood curiosity. Qualitative research with literature study method uses a population of all Indonesian PAUD literature from 2017-2025, purposive sample of 20-30 high-citation sources. Instruments include literature review guidelines, data collection via keyword searches, analysis following Miles and Huberman model with source triangulation. Results reveal simple science experiments boost children's enthusiasm, spontaneous questions, cause-effect thinking, and holistic development in cognitive, language, and socio-emotional domains. Conclusions affirm this approach as essential for active learners, with implications for teacher training and play-based curricula